2014
DOI: 10.2466/03.20.pr0.114k22w4
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Emotion Regulation and Mental Health: A Meta-Analysis Review

Abstract: This meta-analysis examined the relationship between emotion regulation strategies (cognitive reappraisal, expressive suppression) and mental health (measured by life-satisfaction, positive affect, depression, anxiety, and negative affect). 48 studies, which included 51 independent samples, 157 effect sizes, and 21,150 participants, met the inclusion criteria. The results showed that cognitive reappraisal was correlated significantly and positively with positive indicators of mental health (r = .26) and negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
378
4
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(415 citation statements)
references
References 59 publications
(41 reference statements)
23
378
4
10
Order By: Relevance
“…Empirical evidence suggests the existence of an association between the use of reappraisal and increased expression of positive emotion, increased interpersonal functioning, and increased wellbeing when compared to other forms of regulation, such as behavioral suppression (Gross, 2002;Gross & John, 2003). Moreover, reappraisal has been shown to be positively associated with mental health, and negatively with emotional disorders Hu et al, 2014;Joormann & Gotlib, 2010). Among the relatively less adaptive emotion regulation strategies, suppression is one of the most investigated.…”
Section: Maladaptive Consequences Of Cognitive Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical evidence suggests the existence of an association between the use of reappraisal and increased expression of positive emotion, increased interpersonal functioning, and increased wellbeing when compared to other forms of regulation, such as behavioral suppression (Gross, 2002;Gross & John, 2003). Moreover, reappraisal has been shown to be positively associated with mental health, and negatively with emotional disorders Hu et al, 2014;Joormann & Gotlib, 2010). Among the relatively less adaptive emotion regulation strategies, suppression is one of the most investigated.…”
Section: Maladaptive Consequences Of Cognitive Controlmentioning
confidence: 99%
“…Compared to reappraisal, suppression has been negatively associated to the expression of positive emotion, effective interpersonal functioning, and well-being (Gross, 2002;Gross & John, 2003). Moreover, suppression is negatively correlated with mental health indicators (Hu et al, 2014), and its habitual use has been observed in patients with depression and anxiety diagnoses .…”
Section: Maladaptive Consequences Of Cognitive Controlmentioning
confidence: 99%
“…Emotional regulation via cognition such as cognitive reappraisal and expressive suppression are shown to lead to better social adjustment, mental health and overall wellbeing [64] . Furthermore, cognitive training in patients with psychiatric disorders (schizophrenia, attention deficit hyperactivity disorder, mood disorders and substance use disorders) could improve emotional regulation, clinical symptoms, and adaptive community functioning [65] .…”
Section: Emotion and Cognitionmentioning
confidence: 99%
“…Confrontation or the expression of emotion to those responsible for the negative emotions, with the aim of changing what happened, is usually dysfunctional or neutral in the case of negative affect (Penley et al, 2002). Also, inhibition of feelings and suppression of expressions are dysfunctional forms of emotional regulation for negative affect (Gross, 2005, 2015; Hu et al, 2014), and are negatively associated with well-being (Gross and John, 2003). Both are related to affect balance, r = -0.16 and r = -0.18 (PĂĄez and Da Costa, 2014) and suppression is associated with EI, r = -0.21 (Peña-Sarrionandia et al, 2015).…”
Section: Introductionmentioning
confidence: 99%